Myricetin Improves Impaired Nerve Functions in Experimental Diabetic Rats - Ma, Junxiong; Liu, Jun; Chen, Yu; Yu, Hailong; Xiang, Liangbi (Frontiers in Endocrinology, 2022)
Diabetic peripheral neuropathy (DPN) is considered as one of the most important complications of diabetes mellitus. At present, effective treatments which might improve the damaged neurological function in DPN are sorely needed. As myricetin has been proved to possess excellent neuroprotective and antioxidant effects, it might have therapeutic potential for DPN. Therefore, the purpose of our study was to detect the potential beneficial effect of myricetin on DPN. A single dose of 50mg/kg of streptozotocin was applied in rats for the establishment of diabetic models. Different dose of myricetin (0.5 mg/kg/d, 1.0mg/kg/d and 2.0 mg/kg/d) was intraperitoneally injected for 2 weeks from the 21st day after streptozotocin injection. After the final myricetin injection, behavioral, electrophysiological, biochemical and protein analysis were performed. In the present study, myricetin significantly ameliorated diabetes-induced impairment in sensation, nerve conduction velocities, as well as nerve blood flow. In addition, myricetin significantly reduced the generation of advanced glycation end-products (AGEs) and reactive oxygen species (ROS), elevated Na+, K+-ATPase activity and antioxidants activities in nerves in diabetic animals. Additional studies revealed that myricetin significantly raised the hydrogen sulphide (H2S) levels, elevated the expression level of heme oxygenase-1 (HO-1) as well as nuclear factor-E2-related factor-2 (Nrf2) in diabetic rats. The findings in our present study collectively indicated that myricetin could restore the impaired motor and sensory functions under diabetic condition. Nrf2-dependent antioxidant action might be the underlying mechanism of the beneficial effect of myricetin on impaired neural functions. Our study showed the therapeutic potential of myricetin in the management of DPN.